Legal politics of criminal law against the revival of death penalty as an alternative punishment in the new criminal code - Kadir, Abdul; Santiago, Faisal; Achmad, Suparji; Redi, Ahmad (International Journal Labs, 2024)
The reform of the death penalty into an alternative crime in the new Criminal Code (Law Number 1 of 2023 pertaining to the Criminal Code) is a long-standing agenda that has been launched by the Indonesian Government. This paper aims to analyze how Indonesian criminal law is currently enforced to determine how it will be implemented in the future. This research focuses on the politics of criminal law and basic freedoms regarding the reform of capital punishment into an alternate crime in Law No. 1 of the Republic of Indonesia (KUHP) 2023. The study is based on literature studies and documentation. The results of this study show that, despite the fact that KUHP is primarily intended to protect society, its application should be cautious and targeted at the offender; consequently, it must be selective, and there should be provisions for conditional death sentences or delaying the execution of the penalty.